Ketimpangan Gender Dalam Kajian Keagamaan Dewan Dakwah Lampung - Masykuroh, Siti; Sudarman, Sudarman (AL-ADYAN, 2020)
Public religious learning regularly held by Dewan Dakwah Lampung (Dakwah Council of Lampung) often contains issues of women and gender. Yet, their understanding of gender and women issues is largely influenced by religious interpretations, cultural stereotypes and juridical facts which do not preside with women, so that many of their advises on women issues are laden with gender inequalities. This is at odds with Islamic tenets on values of equality and respect to human dignity, irrespective of gender difference.  On the basis of this problem, there is a need to redesign the contents of religious learning, one that is free from gender bias and is based on the gender quality principles. This effort then should be manifested in the form of learning modules, representing religious messages that are gender-equality-friendly, written in a persuasive language, printed in a charming style, and then spread to religious believers. This effort is important   because historical facts have pointed to  the seclusion of  women  in and by many traditions. Thus, if more chances are given to women to compete with men in a sportive manner, it is more likely that they will achieve as many prosperity as their men peers do.